The role of gut microbiota-derived metabolites in modulating poultry immunometabolism - Oke, O. E.; Fasasi, L. O.; Opowoye, I. O.; Akosile, O. A. (Frontiers in Physiology, 2025)
The poultry sector is crucial to global food security, but it faces increasing challenges from heat stress, viral diseases, and restrictions on antibiotic use. These stressors highlight immunometabolism, the junction of immune function and metabolic pathways, as a crucial factor in determining the productivity and health of poultry. There is growing evidence that the gut microbiota is a dynamic metabolic organ that produces a diverse range of bioactive metabolites in addition to its function in nutritional digestion. The immunometabolism of poultry is significantly influenced by these microbiota-derived metabolites, including short-chain fatty acids, bile acid derivatives, amino acid catabolites, vitamins, and polyamines. Disease resistance, vaccination responsiveness, and stress adaptability are shaped by their modulation of intestinal barrier integrity, energy balance, oxidative stress resilience, and immune cell activation. This review summarises what is currently known about the functional diversity and composition of the gut microbiota in poultry, describes the concept of immunometabolism in birds, and assesses the mechanisms by which microbial metabolites regulate metabolic and immunological crosstalk. Prebiotics, probiotics, synbiotics, postbiotics, phytochemicals, and other nutritional and managerial interventions that improve advantageous metabolite profiles are given particular consideration. Applications to enhance poultry health, alleviate heat stress, reduce reliance on antibiotics, and promote sustainable production are also discussed. For mapping metabolite–immune interactions, emerging methods such as germ-free models, metabolomics, metagenomics, and systems biology approaches are emphasised as revolutionary. Metabolites produced by the gut microbiota are crucial to poultry immunometabolism and offer promising opportunities for precision nutrition and healthcare. Bridging the existing research gaps using integrative, multidisciplinary methods to promote sustainable and resilient poultry production is needed. This review centres on the mechanistic axis linking gut microbiota-derived metabolites to host immunometabolic regulation, tracing the pathway from metabolite generation through receptor activation and immune–metabolic reprogramming to measurable phenotypic outcomes in poultry.